2017
DOI: 10.3389/fpsyg.2017.00837
|View full text |Cite
|
Sign up to set email alerts
|

Visible Social Interactions Do Not Support the Development of False Belief Understanding in the Absence of Linguistic Input: Evidence from Deaf Adult Homesigners

Abstract: Congenitally deaf individuals exhibit enhanced visuospatial abilities relative to normally hearing individuals. An early example is the increased sensitivity of deaf signers to stimuli in the visual periphery (Neville and Lawson, 1987a). While these enhancements are robust and extend across a number of visual and spatial skills, they seem not to extend to other domains which could potentially build on these enhancements. For example, congenitally deaf children, in the absence of adequate language exposure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 70 publications
1
7
2
Order By: Relevance
“…While our results suggest that even relatively short delays can delay the development of ToM-selective responses in RTPJ, from our results alone, it is unclear how much linguistic experience is sufficient to overcome this delay or if there is a sensitive period for the impact of linguistic experience on ToM. Prior behavioral studies have found evidence for enduring ToM delays in adults who received access to language after longer delays (i.e., after age 10 years) [91][92][93] , but there is also evidence that ToM delays can resolve with subsequent linguistic experience 33,68,91,94 . Here, we did not observe an enduring effect of delayed access to language on RTPJ selectivity in adults.…”
Section: Discussioncontrasting
confidence: 48%
“…While our results suggest that even relatively short delays can delay the development of ToM-selective responses in RTPJ, from our results alone, it is unclear how much linguistic experience is sufficient to overcome this delay or if there is a sensitive period for the impact of linguistic experience on ToM. Prior behavioral studies have found evidence for enduring ToM delays in adults who received access to language after longer delays (i.e., after age 10 years) [91][92][93] , but there is also evidence that ToM delays can resolve with subsequent linguistic experience 33,68,91,94 . Here, we did not observe an enduring effect of delayed access to language on RTPJ selectivity in adults.…”
Section: Discussioncontrasting
confidence: 48%
“…While our results suggest that even relatively short delays can delay the development of ToMselective responses in RTPJ, from our results alone, it is unclear how much linguistic experience is sufficient to overcome this delay or if there is a sensitive period for the impact of linguistic experience on ToM. Prior behavioral studies have found evidence for enduring ToM delays in adults who received access to language after longer delays (i.e., after age ten years) [91][92][93] , but there is also evidence that ToM delays can resolve with subsequent linguistic experience 33,68,91,94 . Here, we did not observe an enduring effect of delayed access to language on RTPJ selectivity in adults.…”
contrasting
confidence: 49%
“…Rather, our evidence comes from adults, who already have fully fledged language abilities a fully fledged theory of mind. The role of language in the development of ToM remains debated, with some arguing that language may be required to form an understanding of false beliefs (e.g., Gagne & Coppola, ; Pyers & Senghas, ; de Villiers, ), while others have found evidence to suggest otherwise, whether from linguistically impaired humans (e.g., Varley & Siegal, ; Varley et al., ) or nonhuman animals (e.g., Krupenye et al., ). Our data, coming exclusively from adults with normal language abilities, is not in a position to inform these debates.…”
Section: Discussionmentioning
confidence: 99%